2022
DOI: 10.1177/11786361221104446
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Antimicrobial Resistance Profiles of Bacterial Aetiologies of Childhood Otitis Media in Accra, Ghana

Abstract: Background: Otitis media (OM), also known as middle ear infection, is a clinically significant childhood disease. In sub-Saharan Africa, there is a paucity of contemporary reports on it is bacterial aetiologies and antimicrobial resistance among them. Aim: To investigate the OM bacterial aetiologies and their antimicrobial resistance patterns among children visiting the Ear, Nose, and Throat clinics of 3 healthcare facilities in Accra, Ghana – Princess Marie Louise Children’s Hospital, 37 Military Hospital, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
3
4
0
Order By: Relevance
“…This finding is similar to that of study performed in Dessie, Ethiopia, which reported 89.4% (28) but it was higher than that of studies done in Gondar (76.7%) and Bahir Dar (80.4%) (14,29). In contrast, the current culture positivity rate was lower than that studies performed in Ghana (97%) and India (95.7%) (30,31), which may be related to variations in the availability of isolation and identification media. This may be correlated with the fact that availability of relevant media and other supplies maximizes the frequency of culture positivity in middle ear discharge.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This finding is similar to that of study performed in Dessie, Ethiopia, which reported 89.4% (28) but it was higher than that of studies done in Gondar (76.7%) and Bahir Dar (80.4%) (14,29). In contrast, the current culture positivity rate was lower than that studies performed in Ghana (97%) and India (95.7%) (30,31), which may be related to variations in the availability of isolation and identification media. This may be correlated with the fact that availability of relevant media and other supplies maximizes the frequency of culture positivity in middle ear discharge.…”
Section: Discussionsupporting
confidence: 84%
“…Studies from other parts of Ethiopia used different antibiotics and reported varying susceptibility patterns (25,35). Studies from other parts of the world tested different antibiotics with varying susceptibility patterns (30,36,44) with one of the studies (30) that tested piperacillin-tazobactam, ciprofloxacin and ceftazidime, which were also tested in this study. The use of different antibiotics in different studies is attributed to the occasional emergence of resistant strains from time to time, the availability of proposed antibiotics and local prescribing practices.…”
Section: Discussionmentioning
confidence: 99%
“…The high antibiotic resistance levels recorded in the present study (in which the isolates investigated were collected nearly eight years ago) are similar to those observed among Enterobacterales in several other studies conducted in Ghana, both older [11,13,24], and newer ones [32][33][34][35][36][37]. That the high AMR levels observed in this study are similar to those in these newer studies [32][33][34][35][36][37] suggests that the AMR situation in the country has been sustained, or possibly been exacerbated over the period, and could probably get worse. A meta-analysis may be needed to quantify the dynamics in the AMR problem in the country in the last decade or two; this could be done in other regions noted as hotspots for AMR occurrence.…”
Section: Plos Onesupporting
confidence: 90%
“…Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae) are two of the major gutcolonizing Gram-negative bacilli of the Enterobacterales implicated in meningitis, infections of the gastrointestinal and urinary tracts, septicaemia, and other infections, most of which are multidrug resistant (MDR) [1][2][3][4][5]. Such resistance traits have a global distribution, and threaten the efficacy of antibiotics [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%